A Contrastive Study of Four English Versions of Labor Contract Law of the People’s Republic of China - Zhang, Mao (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
Law is a system of rules of conduct that are created by the national legislature in accordance with the legislative procedures and are enforced by the state power. Legal language, as the manifestation of law and the carrier of the legal information, must be accurate and formal. On the ground of the special function of law, words are dedicatedly selected and used within the given field in legal texts. Some unique lexical features of legal language can be found easily to ensure the accuracy and formalness of legal texts, such as the employment of archaic words, the use of loan words and the application of formal words. The contrastive study is conducted from the lexical aspect of the four English versions of Labor Contract Law of the People’s Republic of China, with an attempt to find out the differences in formalness of the law caused by different uses of words in four versions and wish legal translators pay more attention to formality and accuracy of legal words. As for the four versions, one is taken from PKU’s legal academic sector, marked as V1 in the following comparative study. One is translated by Backer & Mckenzie(V2), one of the biggest legal agents in the world, which functions as an introduction of Chinese government’s policies concerning labor contracts to the world. One is taken from the official website the National People’s Congress of the People’s Republic of China (NPC), marked as V3. And the other is taken from Shuangcheng Attorneys at Law in association with China Axis Limited, marked as V4 in the following contrastive study.